Simulation of dual stage thulium-doped fiber amplifier using pump power distribution technique - Muhammad Syauqi Kusyairi bin Jamalus; Nelidya Md. Yusoff; Abdul Hadi Sulaiman (Institute of Advanced Engineering and Science, 2019)
This paper shows dual stage thulium-doped fiber amplifiers (TDFAs) that use a pump power distribution technique. Simulations were done with signals ranging from 1975 nm to 2000 nm using the OptiSystem v.13 software. The results required were gathered from the software. The results of gain, noise figure, optical signal-to-noise ratio (OSNR) and output power were obtained. The highest gain and lowest noise figure results were achieved for the double pass dual stage TDFA configuration with values of 19.85 dB and 5.58 dB respectively, followed by the single pass dual stage TDFA. The OSNR and output power performances were also better for the double pass dual stage TDFA, obtaining 57.12 dB and 19.55 dBm respectively. This study shows that thulium can be used in the 2 µm region as an active gain medium and the dual stage architecture and distributed pumping technique proves to be effective techniques to obtain the desired results. Experimental work will be done in the future with the simulated results used as a reference.